Mortality predictors in acute kidney injury patients who underwent continuous venovenous hemodiafiltration: A retrospective, single-center study - Alper Alp; Hakan Akdam; Harun Akar; Yavuz Yeniçerioğlu (Ukrainian Journal of Nephrology and Dialysis, 2021)
Continuous renal replacement therapy (CRRT) is an increasingly preferred treatment that is easier to use in patients with hemodynamic impairment and can be applied in critical care settings. There are various subtypes of CRRT, one of which is continuous venovenous hemodiafiltration (CVVHDF). In this study, we examined the general characteristics of intensive care patients who underwent CVVHDF.Methods. The clinical and biochemical data of 123 patients who underwent CVVHDF in the intensive care units of our center between February 2012 and November 2014 were analyzed retrospectively. Patients who died during the course of therapy were compared with those who survived.Results. The study included 123 patients, 73 males (59.3%) and 50 females (40.7%). The mean age was 64.4 years. Eighty-eight patients (71.5%) died during CVVHDF while 35 patients survived (28.5%). Hemodynamic parameters such as systolic and diastolic arterial blood pressure, mean arterial pressure, and pulse pressure were significantly lower in patients who died compared to survivors (p<0.001). Mean lactic acid level was significantly higher in the deceased group than in the surviving group (8.54 mmol/L vs. 3.68 mmol/L, p<0.001, chi-square test).Conclusions. Low bicarbonate level, low systolic arterial blood pressure, and older age were significant independent predictors of mortality in this study. Mortality rates were significantly higher among patients with lactic acidosis and those over 66 years of age. Lactic acid levels can be used to predict mortality in patients undergoing CVVHDF.